The structure of the integrin αIIbβ3 transmembrane complex explains integrin transmembrane signalling - Lau, Tong-Lay (Nature Publishing Group, 2009)
Heterodimeric integrin adhesion receptors regulate cell migration, survival and differentiation in metazoa by communicating signals bi-directionally across the plasma membrane. Protein engineering and mutagenesis studies have suggested that the dissociation of a complex formed by the single-pass transmembrane (TM) segments of the α and β subunits is central to these signalling events. Here, we report the structure of the integrin αIIbβ3 TM complex, structure-based site-directed mutagenesis and lipid embedding estimates to reveal the structural event that underlies the transition from associated to dissociated states, that is, TM signalling. The complex is stabilized by glycine-packing mediated TM helix crossing within the extracellular membrane leaflet, and by unique hydrophobic and electrostatic bridges in the intracellular leaflet that mediate an unusual, asymmetric association of the 24- and 29-residue αIIb and β3 TM helices. The structurally unique, highly conserved integrin αIIbβ3 TM complex rationalizes bi-directional signalling and represents the first structure of a heterodimeric TM receptor complex.